2007
DOI: 10.1149/1.2713662
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation of Size-Controlled InP Nanostructures Using Anodic and Cathodic Reactions

Abstract: A two-step electrochemical process using anodic and cathodic reactions was developed to form size-controlled nanostructures on InP͑001͒ substrates. After anodic formation of a nanopore array, the cathodic decomposition process was applied to reduce the thickness of InP nanowalls. The etching rate of the nanowalls was extremely small and strongly dependent on the cathodic bias and crystal orientations of the wall surface. Wall thickness could be controlled in the range of 10-30 nm by changing the cathodic bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…It is important to remember that the pore shape was a square defined by four equivalent ͕100͖ planes, which is similar to the shape of the porous structures after the cathodic decomposition process. 17 This similarity is due to the strong dependence of the etching rate on crystal orientation, where the ͕100͖ planes preferentially appeared on the wall surface due to their slow etching rate. The lateral thickness of the InP nanowalls was less than 20 nm near the surface, which is thinner than the initial value of the template porous sample.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…It is important to remember that the pore shape was a square defined by four equivalent ͕100͖ planes, which is similar to the shape of the porous structures after the cathodic decomposition process. 17 This similarity is due to the strong dependence of the etching rate on crystal orientation, where the ͕100͖ planes preferentially appeared on the wall surface due to their slow etching rate. The lateral thickness of the InP nanowalls was less than 20 nm near the surface, which is thinner than the initial value of the template porous sample.…”
mentioning
confidence: 95%
“…[15][16][17] The nanopores were laterally separated by InP nanowalls several tens of nanometers thick and formed in a straight vertical direction greater than several tens of micrometers. We previously reported that pore diameter and wall thickness can be controlled by adjusting the electrochemical anodic and cathodic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 We have recently reported that InP porous nanostructures showed low photoreflectance and high photoabsorption, 18,19 which are very promising features for porous nanostructures used in the photoelectric conversion devices such as photodetectors and solar cells. Besides, the electrochemical process is applicable to various semiconductors, [20][21][22][23][24] even chemically stable materials such as GaN, [25][26][27][28][29] without causing processing damage. The electrochemical conditions including applied bias and electrolyte solutions have been investigated with regard to the formation of GaN porous nanostructures, but most of the previous studies targeted structural properties and only a few reported on the correlation between the conditions and the resultant optical properties.…”
mentioning
confidence: 99%
“…26 Here, pore diameter and wall thickness can be controlled by adjusting the electrochemical anodic and cathodic conditions. 27 After that, the porous surface was photoelectrochemically etched in the same electrolyte under illumination to remove the disordered irregular layer formed at the initial stage of pore formation.…”
Section: Methodsmentioning
confidence: 99%